Predictors of Early Response and Relapse in Chronic Spontaneous Urticaria Treated with Omalizumab: The Role of Age, Sex, Disease Duration, and UAS7 - Güner, Mehmet Enes; Ozturk, Perihan; Yaray, Ozan Can; Evran Kılıç, Esra Merve; Kuş, Mine Müjde (Dermatology Practical & Conceptual, 2025)
Introduction: Omalizumab is an established treatment for chronic spontaneous urticaria (CSU), yet variability in therapeutic response remains a clinical challenge. Identifying baseline predictors of early response may help optimize patient selection and management strategies.Objectives: To evaluate the predictive value of age, sex, baseline disease severity, and disease duration for early response to omalizumab and to assess their relationship with relapse risk.Methods: This retrospective study included 274 patients with CSU treated with omalizumab between 2011 and 2024. Early response was defined as achieving a UAS7 score <7 at one month. Baseline variables included age, sex, UAS7, and disease duration. Binary logistic regression and ROC curve analyses were conducted to identify independent predictors of early response.Results: Among 274 patients (mean age 42.96±15.54 years; 66.4% female), early response was achieved in 37.6%. Early responders had significantly lower baseline UAS7 and shorter disease duration (both P<0.001). Logistic regression confirmed both variables as independent predictors. Age and sex were not independently associated with early response, although univariate analysis showed a higher early response rate in patients aged <45 years. ROC analysis demonstrated strong inverse predictive value for UAS7 (AUC=0.917) and disease duration (AUC=0.940). Relapse risk was significantly lower in females and patients aged <45 years.Conclusions: Lower baseline UAS7 and shorter disease duration independently predict early response to omalizumab. Younger age and female sex may be associated with lower relapse risk. These findings support earlier therapeutic intervention in patients with lower disease burden to improve outcomes.